2022
DOI: 10.3390/antiox11050961
|View full text |Cite
|
Sign up to set email alerts
|

18β-Glycyrrhetinic Acid Protects against Cholestatic Liver Injury in Bile Duct-Ligated Rats

Abstract: 18β-Glycyrrhetinic acid is a nutraceutical agent with promising hepatoprotective effects. Its protective mechanisms against cholestatic liver injury were further investigated in a rodent model of extrahepatic cholestasis caused by Bile Duct Ligation (BDL) in rats. The daily oral administration of 18β-Glycyrrhetinic acid improved liver histology, serum biochemicals, ductular reaction, oxidative stress, inflammation, apoptosis, impaired autophagy, and fibrosis. 18β-Glycyrrhetinic acid alleviated the BDL-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Among these plant metabolites, chlorogenic acid, scoparone, isoliquiritigenin, glycyrrhetinic acid, formononetin, atractylenolide I, and benzoylaconitine exhibited inhibitory effects on PDGFRβ mRNA expression. Previous studies reported that chlorogenic acid, scoparone, liquiritigenin, and glycyrrhetinic acid exhibit hepatoprotective effects against liver fibrosis ( Hui et al, 2020 ; Wang et al, 2021c ; Miao et al, 2022 ; Pan et al, 2022 ). These active plant metabolites may contribute to the protective effect of YCZFD against DDC-induced CLF by regulating PDGFRβ.…”
Section: Discussionmentioning
confidence: 99%
“…Among these plant metabolites, chlorogenic acid, scoparone, isoliquiritigenin, glycyrrhetinic acid, formononetin, atractylenolide I, and benzoylaconitine exhibited inhibitory effects on PDGFRβ mRNA expression. Previous studies reported that chlorogenic acid, scoparone, liquiritigenin, and glycyrrhetinic acid exhibit hepatoprotective effects against liver fibrosis ( Hui et al, 2020 ; Wang et al, 2021c ; Miao et al, 2022 ; Pan et al, 2022 ). These active plant metabolites may contribute to the protective effect of YCZFD against DDC-induced CLF by regulating PDGFRβ.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhetinic acid (GA), which has an oleanolane-type skeleton, is a pentacyclic triterpene component in Glycyrrhize glabra L extract, a traditional Chinese medicine, and is widely distributed in nature. With multiple biological activities such as anti-infammatory [1], anti-tumor [2,3], antioxidant [4], liver protection [5,6], and enhanced cellular immune regulation [7], GA has signifcant curative efects on ventricular arrhythmias induced by various reasons, can protect myocardium, and can reduce myocardial ischemic damage for acute myocardial infarction [8]. Te biological role of GA in improving lung function has been confrmed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the function of carbohydrate transport and metabolism is significantly decreased by glycyrrhizic acid. Glycyrrhetinic acid prevents cholestatic liver injury in bile duct–ligated rats, while liquiritin alleviates cyclophosphamide-induced liver sinusoidal endothelial injury and inflammatory injury in mice ( Chen M. et al, 2019 ; Pan et al, 2022 ; Wang et al, 2022 ). Poria cocos (Schw.)…”
Section: Introductionmentioning
confidence: 99%